Drying behaviour of food waste and leftovers for trench composting - Khalida, Aziz (2022)
With the global population growth of 7.6 billion, food waste has affected the environment, and the economy gradually, which has recently received much attention worldwide. Food waste recycling is a vital waste management parameter in the household and food processing industry. This study aims to describe the kinetics of drying food waste and leftovers and their usage as raw materials in trench compost to improve soil quality in terms of pH value, electric conductivity (EC), and nutrient concentrations while reducing leachate and greenhouse gas emissions. The collected food waste and leftovers were equally divided for the pretreatment procedure. The samples were subjected to the soaking process in warm distilled water at 70°C for five minutes and the remaining were left untreated. Subsequently, both pretreated and non-pretreated food waste and leftovers were subjected to hot air drying at 80°C, 90°C, and 100°C. Dried samples were then subjected to trench composting by mixing with garden soil according to a 5/3 ratio. According to the findings, the air temperature and pre-treatment substantially impacted the dehydration rate, effective diffusivity, activation energy, and nutrient content, pH value, and EC in the final products of trench compost. The final product of pretreated dried leftover at 800C after trench compost had the highest value of C, N, H, and S (36.53) %, and, micronutrient (K =880.1 mg/L, Ca= 83.99 mg/L, Cu= 1.88 mg/L, Mg =53.12 mg/L, and Zn=14.95 mg/L) compare to pretreated dried food waste at 800C after trench compost. While final product dried of food waste at same condition had 29.73% total of CNHS, and micronutrient (K =392.2 mg/L, Ca= 109.8 mg/L, Cu= 0.98 mg/L, Mg =58.35 mg/L, and Zn=11.4 mg/L). Overall, the nutrient content of dehydrated leftovers after trench compost was premised to improve soil quality. In conclusion, the dehydrated food waste and leftovers retard decomposition and minimize odor, allowing for more frequent waste collection.